Local wisdom in the traditional game PÈRÈPÈT JÈNGKOL as strengthening the character of elementary school students - Rahmawati, Agustina; Sylviani, Amelia; Anisah, Anisah; Tarmidzi, Tarmidzi; Putri, Dian Permana (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
The aim of this research is to determine students' character using the traditional game media pérèt jèngkol. This research is descriptive research that uses case studies. This game was played for 6 days (6 meetings) and researchers used observation sheets and videos to "see" how students' characters developed during play from the first day to the following days. After carrying out observation activities, the data taken from the observation sheet and video will be rearranged by the researcher and then grouped into existing tables. A person's character must be formed when they are still small, so that they are more accustomed to doing positive things. In the modern era like now, children experience a decline in character values, because there are so many negative things they can see and imitate. Other negative things include a lack of social skills and direct communication, because too much time is spent playing with gadgets, a lack of patience in children in facing challenges so they have difficulty concentrating on certain tasks or activities, children will also become dependent on gadgets so they Loss of interest in playing outdoors. To overcome this problem, researchers want to examine how the character changes experienced by students in elementary schools by playing the traditional game PÈRÈPÈT JÈNGKOL ngkol. The conclusion is that observing the character of elementary school children can be done through several efforts, such as playing the traditional game pérèt jèngkol. Apart from that, this way can also preserve culture